2013
DOI: 10.1103/physrevb.88.024119
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of phase stability and crystal structures in Li-Zn mixed-metal borohydrides

Abstract: We address the problem of finding mixed metal borohydrides with favorable thermodynamics and illustrate the approach using the example of LiZn 2 (BH 4 ) 5 . Using density functional theory (DFT), along with the grand canonical linear programming method (GCLP), we examine the experimentally and computationally proposed crystal structures and the finite-temperature thermodynamics of dehydrogenation for the quaternary hydride LiZn 2 (BH 4 ) 5 . We find the following: (i) For LiZn 2 (BH 4 ) 5 , DFT calculations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…• C) as well as reversibility [9] triggered extensive research on hydrogen release and decomposition pathways of complex metal hydrides [3,[10][11][12]. In particular, two complex hydrides systems attracted intense interest: 1) The first involves Mg(BH 4 ) 2 , which contains 14.9%…”
Section: Introductionmentioning
confidence: 99%
“…• C) as well as reversibility [9] triggered extensive research on hydrogen release and decomposition pathways of complex metal hydrides [3,[10][11][12]. In particular, two complex hydrides systems attracted intense interest: 1) The first involves Mg(BH 4 ) 2 , which contains 14.9%…”
Section: Introductionmentioning
confidence: 99%
“…The lattice constants and ion positions are optimized using the Broyden-Fletcher-Goldfarb-Shanno (BFGS) quasi-Newton algorithm with the force convergence criterion less than 10 −3 eV/Å. The vibrational entropy is calculated using vib = , where ω is the vibrational frequency, q the wave vector, and v the index of the phonon mode 46 . Here we should point out that we calculated the phonon and vibrational entropy with ignoring the thermal expansion effect, since the calculations incorporating the thermal expansion effect would require the third-order force constants, which is quite time-consuming for the C 18 H 38 supercell.…”
Section: Methodsmentioning
confidence: 99%
“…10) with pressure present a high consistency with the experiment results 26,27 This indicates the rationality of the relevant models and parameters adopted in the present MD simulation. The previous studies definitely indicate that DFT is highly reliable in estimating the lattice vibration entropy (Svib) of crystalline materials 46 . Therefore, the Svib of C18H38 in solid state was estimated by this mean and compared with the total entropy (St) obtained by experiments.…”
mentioning
confidence: 96%
“…A first-principle study (DFT + PEGS (prototype electrostatic ground state)) indicated that LiZn(BH 4 ) 3 would have a triclinic C1 space group symmetry [ 146 ]. LiZn(BH 4 ) 3 is calculated to be more stable (about −8 kJ/mol cation) as compared to the parent borohydrides of Li and Zn [ 146 ], but unstable towards decomposition to LiBH 4 and LiZn 2 (BH 4 ) 5 (from DFT along with grand canonical linear programming method) [ 158 ]. In turn, LiZn 2 (BH 4 ) 5 is calculated to decompose in a rather complex pathway [ 158 ]: LiZn 2 (BH 4 ) 5 → 2Zn + 1/5 LiBH 4 + 2/5 Li 2 B 12 H 12 + 36/5 H 2 → 2Zn + 1/6 LiH + 5/12 Li 2 B 12 H 12 + 89/12 H 2 → 11/6 Zn + 1/6 LiZn + 5/12 Li 2 B 12 H 12 + 15/2 H 2 → Zn + 5B + LiZn + 10H 2 …”
Section: Transition Metal Borohydridesmentioning
confidence: 99%